2019
DOI: 10.1016/j.wnsx.2019.100022
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Magnetic Resonance Imaging–Guided Glioma Resections in Awake or Asleep Settings and Feasibility in the Context of a Public Health System

Abstract: Background Despite the most recent surgical aids and tools, surgical removal of infiltrating brain tumors remains a challenge. Unclear margins, edematous areas, and infiltrative behavior are the main causes for failing gross total removals. Also, excessive resection of peri-tumoral tissue often carries risks of damaging the nearby functioning cortical and subcortical structures with an unacceptable decrease in patient's quality of life and postoperative functional status, and the risk of making pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
0
19
1
Order By: Relevance
“…Although there is little objection that AC is superior to general anesthesia (GA) for functional preservation, its ability to improve the EOR is controversial. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] One reason making such validation di cult is that many studies have not evaluated the OS, despite the proven strong correlation between EOR and OS, owing to the di culty of adjusting the bias induced by the eloquent areas. The lack of an objective de nition of eloquent areas on the image is a factor, but the most critical one is the selection bias of patients who underwent surgery performed under GA despite eloquent lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is little objection that AC is superior to general anesthesia (GA) for functional preservation, its ability to improve the EOR is controversial. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] One reason making such validation di cult is that many studies have not evaluated the OS, despite the proven strong correlation between EOR and OS, owing to the di culty of adjusting the bias induced by the eloquent areas. The lack of an objective de nition of eloquent areas on the image is a factor, but the most critical one is the selection bias of patients who underwent surgery performed under GA despite eloquent lesions.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Gerritsen et al was also the only one to find a lower rate of late minor postoperative complications with AC than craniotomy under GA. Survival outcome was similar between AC and craniotomy under GA in the studies by Gerritsen et al 33 and Gravesteijn et al, 36 but higher for the AC group in Pichierri et al 35 (4 out of 6 patients alive at an average of 25 months’ follow-up for the AC group vs 1 out of 8 patients alive at 26 months in the GA group). Notably, both groups in the study by Pichierri et al also had iMRI used.…”
Section: Resultsmentioning
confidence: 70%
“…PFS and OS were reported in 5 studies, but the reported data were insufficient or too heterogenous to compute pooled mean estimates. Pichierri et al 35 reported an average PFS of 21 months in 6 GBM patients. Among these 6 patients, all 4 patients who underwent GTR had OS of more than 25 months, while the 2 patients who underwent STR died at 12 and 30 months.…”
Section: Resultsmentioning
confidence: 99%
“…Our PFS is superior to this figure in both cohorts probably due to the coexistence of HGG and LGG in each group. Previous reports evaluating the effectiveness of iMR devices failed to demonstrate significant changes on PFS (36). However, positive trends on the improvement of PFS had been linked to the use of intraoperative imaging tools (10,36,37) as a result of an increase in the EoR (35,38,39).…”
Section: Discussionmentioning
confidence: 99%